Determinan Housing Mobility di Surabaya - Njo Anastasia; Joshua Gondo Kusuma (BISMA (Bisnis dan Manajemen), 2019)
Every individual definitely will perform housing mobility in accordance to pursue his life purpose. This research aims to determine the influence of affordability, life-course, housing profile, and neighborhood to housing mobility decision in Surabaya, Indonesia. Data samples were collected from Surabaya societies who have ever moved before, and living in a self-owned home at the moment. The method of analysis used is Partial Least Square (PLS). The results insinuate that affordability, and housing profile elucidates significant impact on housing mobility. Howbeit, life-course and neighborhood delineate insignificant impact on housing mobility. Therefore, individual's decision to perform a mobility is influenced by availability of wealth and physical appearance of the chosen house to be occupied.